Sea ice loss in association with Arctic cyclones - Steven M. Cavallo; Madeline C. Frank; Cecilia M. Bitz (Communications Earth & Environment)
Abstract Arctic sea-ice extent has reduced by over 40% during late summer since 1979, and the day-to-day changes in sea ice extent have shifted to more negative values. Drivers of Arctic weather that cause large short-term changes are rarely predicted more than a week in advance. Here we investigate variability in changes in sea ice extent for periods of less than 18 days and their association to Arctic cyclones and tropopause polar vortices. We find that these very rapid sea ice loss events are substantial year-round and have increased over the last 30 years in June-August due to thinning sea ice that is more susceptible to forcings from ocean waves and low-level atmospheric wind. These events occur in regions of enhanced near-surface level pressure gradients between synoptic-scale high and low pressure systems over regions of relatively thin sea ice, and are preceded by tropopause polar vortices.